2019
DOI: 10.1002/pcr2.10062
|View full text |Cite
|
Sign up to set email alerts
|

Crystallization kinetics of high‐density and low‐density polyethylene on carbon nanotubes

Abstract: This study presents a comparative analysis of the crystallization behavior of low‐density polyethylene (LDPE) and high‐density polyethylene (HDPE) nanocomposites. Carbon nanotubes (CNTs) were used as a nucleating agent to generate a nanohybrid shish‐kebab architecture. Materials characterizations were performed to evaluate the crystal morphology and crystallization kinetics using scanning electron microscopy (SEM) and differential scanning calorimetry (DSC), respectively. The lamellae of polyethylene were alwa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 63 publications
(84 reference statements)
0
13
0
Order By: Relevance
“…Fundamentally, crystallization involves two stages: nucleation and crystal growth. In our continuous efforts to realize the potential of CNTs to induce polymer crystallization, we found that carbon‐based nanoparticles are effective agents that facilitate nucleation; however, the second stage of growth is governed by space …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fundamentally, crystallization involves two stages: nucleation and crystal growth. In our continuous efforts to realize the potential of CNTs to induce polymer crystallization, we found that carbon‐based nanoparticles are effective agents that facilitate nucleation; however, the second stage of growth is governed by space …”
Section: Resultsmentioning
confidence: 99%
“…In our continuous efforts to realize the potential of CNTs to induce polymer crystallization, we found that carbon-based nanoparticles are effective agents that facilitate nucleation; however, the second stage of growth is governed by space. [31][32][33][34] It has been previously reported that the dimensionality of carbon nanoparticles primarily governs the supramolecular architecture of the crystallized polymer. 24,35 As seen in SEM images of PLA-GNS, the polymer seems to be crystallized randomly on the surface of GNS in multiple orientations to generate a flower-like, petal-shaped structure.…”
Section: Characterization Methodsmentioning
confidence: 99%
“…These results are consistent with the transcrystalline layer deposited in between the adjacent kebabs and on the long axis of CNTs (SEM and TEM results). This transcrystalline layer results into a less compact lamella, hence decrease the crystallite size …”
Section: Resultsmentioning
confidence: 99%
“…The crystallinity or crystallinity index (CI) was determine as per reported protocol. [50][51][52] The CI of the pure polymer was 49%. The value of CI was lowest for 50-50-LMW (21%), slightly higher for 50-50-HMW (51%), intermediary for 20PE-80PEG (54%), and highest for 80PE-20PEG (64%).…”
Section: Crystal Structure Characterization By Xrdmentioning
confidence: 99%
“…On the basis of DSC analyses, Dias and Yerushalmi‐Rozen reported a significant increase in polymer crystallinity in CNT composites. The crystallization kinetics of high‐density and low‐density polyethylenes on CNTs were also investigated by Depan et al . The induced crystallization of P3ATs onto graphenic materials was also widely reported; e.g.…”
Section: Introductionmentioning
confidence: 97%